Respuesta :
Answer:
y = 2x - 1
Step-by-step explanation:
y - 2x + 2 = 1
6x - 3y = 3
[tex]y - 2x + 2 = 1 \\ +2x - 2 +2x - 2\\y = 2x - 1[/tex]
Plug in for y:
6x - 3(2x - 1) = 3
6x - 6x + 3 = 3
Simplified, 3 = 3
Answer: this solution has infinite solutions
Step-by-step explanation:
original system:
y-2x+2 = 1
6x-3y = 3
Move 2 to right side of equation
y -2x = -1
-3y+6x = 3
solve for y in first equation
⇒ y = 2x - 1
insert y into second equation
⇒ -3(2x-1) + 6x = 3
simplify
⇒ -6x+3+6x = 3
simplify once more
⇒ 3 = 3
this solution has infinite solutions